The bread of two worlds: a duoethnography on multilingualism. Issue 1 (2nd January 2018) - Howe, Lori; Khasilova, Dilnoza F.
ABSTRACT: In this duoethnography, Lori Howe, whose familial roots are in Appalachia, and Dilnoza Furkatovna, whose roots are in Uzbekistan, employ the qualitative approach of the mystory to illuminate the thread of multilingualism in our lives, through personal histories, poems, vignettes, and short stories based upon our wildly different cultural and lingual researcher histories. At the center of our experiences, many questions of power, responsibility, and cognitive growth and opportunity are located at the intersections of mono- and multilingualism. Throughout the three sections of this duoethnography, we have woven a review of the literature on the following themes: Multilingualism and Cognitive Development; Inclusiveness of L1 Dialects in Monolingual Classrooms; Multilingual Children: Raising Global Citizens; Inside these three sections, the literature is nested with our creatively-presented lived experiences, histories, and perspectives on the need for multilingualism and inclusiveness of multiple dialects in the global community.